13(x-1)=7x+23

Simple and best practice solution for 13(x-1)=7x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13(x-1)=7x+23 equation:


Simplifying
13(x + -1) = 7x + 23

Reorder the terms:
13(-1 + x) = 7x + 23
(-1 * 13 + x * 13) = 7x + 23
(-13 + 13x) = 7x + 23

Reorder the terms:
-13 + 13x = 23 + 7x

Solving
-13 + 13x = 23 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-13 + 13x + -7x = 23 + 7x + -7x

Combine like terms: 13x + -7x = 6x
-13 + 6x = 23 + 7x + -7x

Combine like terms: 7x + -7x = 0
-13 + 6x = 23 + 0
-13 + 6x = 23

Add '13' to each side of the equation.
-13 + 13 + 6x = 23 + 13

Combine like terms: -13 + 13 = 0
0 + 6x = 23 + 13
6x = 23 + 13

Combine like terms: 23 + 13 = 36
6x = 36

Divide each side by '6'.
x = 6

Simplifying
x = 6

See similar equations:

| 15x=18+13x | | 13y+36=153 | | 8(4s+9)=328 | | -3x-6/4=3 | | y^2-xy-3x=1 | | 1/6x-9=-2 | | 2x-21=5x-3y-12 | | (2x-7)+(3x+4)=0 | | 10x^4=0.001 | | (7/4)(-5) | | 15p+p+-19p+20p+-14p-16=-2 | | 8r+2r-2r-3r-3r=20 | | -5n-(-14n)+-11n+-4n=18 | | 2(x-4)-3(5x-1)=8 | | 7j+6j-12j=17 | | -13h+8h+10h=-20 | | -5x+4x=-20 | | (1-2a)x^2-2ax-1=0 | | 4x^2-29+5x+1=0 | | 9(6x+2)whenx=9 | | (8+i)(7+5i)=0 | | 2*m*n*8= | | 3x+12-5x+10=2x-5x+5 | | q^2-11q+30=0 | | -10x+30=-3x+100 | | 4/x-2=43 | | x^2-8x-15=3x-3 | | x^2+10x+3=7x+1 | | 9x-2=4x+x+4 | | 5/2x=43/4 | | -3x+5=21x | | -122=-6(1-4n)+4 |

Equations solver categories